The Relationship between Buddhist education in Sriwijaya and Buddhist education in India - Diah Wicahyah; Alvian Kisna Asyari; Dedi Irwanto; LR Retno Susanti (Ilomata International Journal of Social Science, 2022)
Development Buddhist education on the island of Sumatra, specifically in the Srivijaya Kingdom, began in the seventh century. At the time, there was a city big a Chinese Buddhist monk I'Tsing who came see that Buddhism was very developed in life Public Srivijaya as well as he said many activity students who come to Srivijaya for study. The purpose of writing this is to have a deeper understanding of the entwined relationship between the Srivijaya Kingdom and India, particularly in the sphere of education. This article will not only analyze the relationship between education and Buddhism in South Sumatra, but will also describe Buddhist education, the relationship that exists between Kingdom Srivijaya and other countries in numerous fields, and provide proofactual links of cooperation in the sphere of Buddhist education that were previously connected The introduction of Hindu-Buddhist culture to Indonesia had a significant impact, such as the beginning of the development of religion and culture imported from India. This method of research is used in article writing to gather knowledge and resources in the form of articles, journals, books, and ebooks. As a result of the research, more detailed information about the entry and development of Buddhism in South Sumatra, as well as the types of relationships and physical evidence, is available.